Euro Area Policies. (IMF Staff Country Reports; Country Report ;, 2004)
The staff report on Euro Area Policies highlights cyclical growth developments and risks. The area's real GDP growth has picked up, responding to strong foreign demand and relaxed financial conditions. The final domestic demand growth remains subdued, and the area lags global growth by a large and widening margin. Euro area corporations have taken considerable time to adjust to the boom-bust cycle in equity valuations. The shared central view is that the export-led recovery will increasingly be sustained by domestic demand growth.